Electrochemical characterization of a new binary oxide of Mo with Co for O2 evolution in alkaline solution - Singh R.N.; Madhu; Awasthi R.; Sinha A.S.K. (My University, 2025)
The α-CoMoO4 oxide has been obtained by a precipitation method and investigated for the first time for electrocatalysis of the oxygen evolution reaction (oer) in alkaline medium. This method produced the pure crystalline CoMoO4 monoclinic phase with crystallite size ∼46 nm and lattice constants: a = 9.666 Å, b = 8.854 Å, c = 7.755 Å and β = 113.82°. The average particle size (based on area density) and the BET surface area of powders of the oxide were 11.58 μm and 9.4 m2 g-1, respectively. Results show that the new oxide is quite active for the oer. Values of the Tafel slope and the reaction order with respect to OH- concentration are observed to be ∼60 mV and ∼1, respectively. © 2008 Elsevier Ltd. All rights reserved.